Novel use of miniature CPC in photovoltaic/thermal and radiative cooling systems - Ya, Dan (2025)
The rapid development of modern society has significantly increased energy consumption, particularly in the building sector. More than 80% of the primary energy supply still relies on non-renewable sources such as fossil fuels, raising concerns about energy shortages and environmental pollution. To promote energy conservation and transition to a sustainable society, research and development of sustainable energy technologies is becoming increasingly imperative. Among various strategies, photovoltaic thermal (PVT) systems, which use solar energy (~5800K) to provide heat and electricity to buildings, and passive radiative sky cooling (RC) technology, which utilizes the cold outer space (~3K) to cool buildings, are seen as attractive approaches. However, RC technology currently faces the challenge of inherent low cooling power, limiting its ability to meet the cooling demands of buildings. Therefore, enhancing the cooling performance of RC technology is urgently needed. Additionally, standalone building-integrated PVT system and RC technology encounter challenges such as seasonal adaptability and single functionality. To effectively integrate PVT and RC systems within a limited building envelope, exploring new configurations is crucial. In this thesis, a concentrated RC system based on a compound parabolic concentrator (named CPC-RC module) is deeply studied and continuously optimizes its structure to enhance cooling performance. Additionally, a hybrid system integrating CPC-RC modules with PVT modules is proposed. This system can simultaneously collect solar energy and cold energy for heating and cooling buildings, aiming to reduce energy consumption and offer an innovative solution for promoting net-zero carbon buildings.